Constraints of zircon U-Pb and biotite Rb-Sr ages and P-T conditions on the emplacement and uplifting of the Late Mesozoic Jinan gabbro, eastern North China. (1st October 2019) - He, Song; Li, Xiang-Hui; Zhang, Hua-Feng; Li, Shuang-Qing; Chen, Fukun
Graphical abstract: Highlights: Jinan gabbro crystallized at ~900 °C in an emplacement depth of ~15–27 km. The magma was derived from an enriched lithospheric mantle at ~130 Ma. This pluton was rapidly uplifted with a cooling rate of ~50 °C/Ma before 120 Ma. This uplift was related to the lithospheric delamination in eastern North China. Abstract: The North China Craton underwent exceptional lithospheric thinning. A debate remains as to the mechanism and timing of this thinning partly as a result of the lack of information on the crustal uplift. Mantle-derived mafic rocks can carry key messages of lithospheric thinning and facilitate the determination of the time and mechanism. Gabbroic rocks from the Jinan area in eastern North China were emplaced in the peak period of the thinning and, for this reason, were chosen as the study object. Isotopic ages and P-T conditions of the Jinan gabbro pluton were measured to examine the uplifting and cooling history of the magma. Jinan gabbros were enriched in large ion lithophile elements and large rare earth elements but depleted in high field strength elements without a significant Eu anomaly. Their Sr-Nd-Pb isotopic features suggest that the magma was derived from the partial melting of an enriched lithospheric mantle (EMI). This pluton was emplaced at ~130 Ma, and crystallization temperatures of pyroxene and biotite were 909–1116 °C and 828–952 °C, respectively. The core and rim crystallization pressures of clinopyroxene and plagioclase are ~4.45 kbar and ~2.56–3.91 kbar, respectively. These might record the pressure changes during the uplift process from ~16.5 to 9.5 km. The Rb-Sr isotopic system of biotite was closed at ~121–117 Ma, constrained by the single–grain biotite Rb-Sr ages. This shows that the cooling depth of pluton is ~8.4 ± 2.4 km. Consequently, the pluton was rapidly uplifted from the ~16.5 km to ~8.4 km, at an uplift rate of 0.81 ± 0.24 km/Ma and/or a cooling rate of approximately 50 °C/Ma during 130–120 Ma. This fast uplift was related to the delamination and thinning of the lithosphere that caused activities associated with magmatism and mineralization in eastern North China during the late Mesozoic.